2000
DOI: 10.1016/s0006-3495(00)76757-9
|View full text |Cite
|
Sign up to set email alerts
|

Proton Electron Nuclear Double Resonance from Nitrosyl Horse Heart Myoglobin: The Role of His-E7 and Val-E11

Abstract: Electron nuclear double resonance (ENDOR) spectroscopy has been used to study protons in nitrosyl horse heart myoglobin (MbNO). (1)H ENDOR spectra were recorded for different settings of the magnetic field. Detailed analysis of the ENDOR powder spectra, using computer simulation, based on the "orientation-selection" principle, leads to the identification of the available protons in the heme pocket. We observe hyperfine interactions of the N(HisF8)-Fe(2+)-N(NO) complex with five protons in axial and with eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 44 publications
(49 reference statements)
3
28
0
Order By: Relevance
“…The spectra were recorded directly after freezing the same amounts of the living cell cultures. The spectra are dominated by an orthorhombic EPR signal, which is typical for a six-coordinated Fe 2ϩ ⅐heme(NO) complex (22)(23)(24)(25)(26)(27)(28)(29)(30). Repeated experiments revealed that for the same quantity of cells, the EPR intensity was found to be a factor 4 -6 higher for the cell cultures overexpressing mutant Ngb than for those overexpressing wt Ngb (see Fig.…”
Section: Expression Cloning and Purification Of Recombinant Wild Typementioning
confidence: 94%
See 3 more Smart Citations
“…The spectra were recorded directly after freezing the same amounts of the living cell cultures. The spectra are dominated by an orthorhombic EPR signal, which is typical for a six-coordinated Fe 2ϩ ⅐heme(NO) complex (22)(23)(24)(25)(26)(27)(28)(29)(30). Repeated experiments revealed that for the same quantity of cells, the EPR intensity was found to be a factor 4 -6 higher for the cell cultures overexpressing mutant Ngb than for those overexpressing wt Ngb (see Fig.…”
Section: Expression Cloning and Purification Of Recombinant Wild Typementioning
confidence: 94%
“…The EPR parameters for type I are given in Table II, the axial g tensor of type II was for all cases taken as g Ќ Ϸ 2.035, g ʈ Ϸ 1.98. The parameters are typical for a six-coordinated Fe 2ϩ (heme)NO structure (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The EPR spectra of the Ngb proteins could be simulated using a ratio of type I over type II (n I /n II ) equal to 80/20%, whereby this ratio was 95/5% for E7-Leu Mb.…”
Section: No Binding To Ngb-mentioning
confidence: 99%
See 2 more Smart Citations
“…ENDOR studies on the A and R isomers of horse heart Mb showed that in the two forms, the NO ligand is stabilized by E7His and E11Val, but that the strength of the interaction is different [41].…”
Section: No Binding To Ferrous Wt Cygbmentioning
confidence: 99%